Kaji Eksperimental Sifat Mekanik Pipa Material Komposit Polyester Berpenguat Serat Daun Nanas - Hendery Dahlan; Islahuddin Islahuddin; Meifal Rusli (Department of Mechanical Engineering, Universitas Andalas, 2018)
Bending stress of a pipe made of natural fiber composite is investigated in this paper. Pineapple leaf which is very potential to be developed as an alternative reinforcement in composite materials is used for this investigation. The effects of layer number and fiber orientation to the bending strength and elastic modulus are investigated. The experiments are conducted based on ASTM D790-03. The results show that the composite pipe with two layers and fiber orientation of 90º/-90º has the highest bending strength. On other hand, the composite material having one layer and fiber orientation of 45º/-45º produce the highest elastic modulus.